Answer:
[tex]-5c[/tex]
Step-by-step explanation:
To find: The sum of [tex]6c-5c[/tex] and opposite of [tex]6c[/tex]
Opposite of [tex]6c[/tex] means taking the opposite sign.
[tex]6c[/tex] is positive. So, opposite sign is [tex]-6c[/tex].
Therefore, the addition is given as:
[tex]=6c-5c+(-6c)[/tex]
Opening the parenthesis, we get:
[tex]6c-5c-6c[/tex]
Now, as per PEDMAS rule, we subtract [tex]6c\ and\ 5c[/tex], we get
[tex]6c-5c=(6-5)c=1c[/tex]
Now, we are left with [tex]1c-6c[/tex]
Subtracting a bigger number from a smaller number will give a negative answer.
So, [tex]1c-6c=(1-6)c=-5c[/tex]
Therefore, the final answer is [tex]-5c[/tex]